2009
DOI: 10.1161/strokeaha.109.548974
|View full text |Cite
|
Sign up to set email alerts
|

Microbleeds Versus Macrobleeds

Abstract: Background and Purpose-Small, asymptomatic microbleeds commonly accompany larger symptomatic macrobleeds. It is unclear whether microbleeds and macrobleeds represent arbitrary categories within a single continuum versus truly distinct events with separate pathophysiologies. Methods-We performed 2 complementary retrospective analyses. In a radiographic analysis, we measured and plotted the volumes of all hemorrhagic lesions detected by gradient-echo MRI among 46 consecutive patients with symptomatic primary lob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
79
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 167 publications
(82 citation statements)
references
References 23 publications
2
79
0
1
Order By: Relevance
“…32,33 According to these criteria probable CAA is defined by the presence of multiple strictly lobar hemorrhages on T2* gradient-recalled echo or susceptibility weighted MRI. These may involve both macrohemorrhages and micro-hemorrhages, 34 herein referred to as 'ICH' and 'microbleeds', respectively. Radiologichistopathologic studies have confirmed that microbleeds often reflect hemosiderin deposits from old microhemorrhages, and sometimes acute extravasations of red blood cells, although not invariably.…”
Section: Pathologic Manifestation Of Cerebral Amyloid Angiopathymentioning
confidence: 99%
“…32,33 According to these criteria probable CAA is defined by the presence of multiple strictly lobar hemorrhages on T2* gradient-recalled echo or susceptibility weighted MRI. These may involve both macrohemorrhages and micro-hemorrhages, 34 herein referred to as 'ICH' and 'microbleeds', respectively. Radiologichistopathologic studies have confirmed that microbleeds often reflect hemosiderin deposits from old microhemorrhages, and sometimes acute extravasations of red blood cells, although not invariably.…”
Section: Pathologic Manifestation Of Cerebral Amyloid Angiopathymentioning
confidence: 99%
“…4,16 Prior symptomatic ICH was defined as a symptomatic stroke syndrome associated with imaging evidence of a corresponding "macro" ICH (.5 mm in diameter on T2*-GRE). 15 Asymptomatic prior ICH (.5 mm in diameter on T2*-GRE MRI) was also noted: chronic ICH was defined on neuroimaging as ICH with no acute bleeding identified on either CT or MRI scans. Acute convexity subarachnoid hemorrhage (cSAH) was defined as linear hypointensity in the subarachnoid space affecting one or more cortical sulci of the cerebral convexities on T2*-GRE sequences with corresponding hyperintensity in the subarachnoid space on T1-weighted or FLAIR images.…”
mentioning
confidence: 99%
“…17 Asymptomatic or symptomatic prior ICH (.5 mm in diameter on T2*-GRE MRI) was also noted. 18 cSS was defined as linear residues of chronic blood products in the superficial layers of the cerebral cortex showing a characteristic "gyriform" pattern of low signal on T2*-GRE images, without corresponding hyperintense signal on T1-weighted or FLAIR images (i.e., without acute subarachnoid hemorrhage). We did not include cSS contiguous with any ICH.…”
mentioning
confidence: 99%